2019
DOI: 10.3390/met9121262
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Hot Deformation Behavior and Processing Maps of Mg-3Sn-2Al-1Zn-5Li Magnesium Alloy

Abstract: The dynamic microstructure evolution of Mg-3Sn-2Al-1Zn-5Li magnesium alloy during hot deformation is studied by hot compression tests over the temperature range of 200–350 °C under the strain rate of 0.001–1 s−1, whereafter constitutive equations and processing maps are developed and constructed. In most of cases, the material shows typical dynamic recrystallization (DRX) features, with a signal peak value followed by a gradual decrease. The value of Q (deformation activation energy) is 138.89414 kJ/mol, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Based on the dynamic material model (DMM), Gegel et al developed a processing map which requires a superimposition of the power dissipation efficiency map and the instability map in the frame of the logarithm of strain rate and deformation temperature [9]. The approach of the dynamic material model has been widely used in various alloys, such as Ni base superalloys [10,11], steels [12][13][14][15], Ti alloys [16,17], Zr alloys [18], Mg alloys [19][20][21][22] and high-entropy alloys [23]. The internal workability for these materials is discussed through the establishment of a processing map.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the dynamic material model (DMM), Gegel et al developed a processing map which requires a superimposition of the power dissipation efficiency map and the instability map in the frame of the logarithm of strain rate and deformation temperature [9]. The approach of the dynamic material model has been widely used in various alloys, such as Ni base superalloys [10,11], steels [12][13][14][15], Ti alloys [16,17], Zr alloys [18], Mg alloys [19][20][21][22] and high-entropy alloys [23]. The internal workability for these materials is discussed through the establishment of a processing map.…”
Section: Introductionmentioning
confidence: 99%
“…The calculated value was lower than those of the rolled single α-phase Mg–Li alloy (211 kJ/mol) [ 24 ], as-cast LAZ532 (160 kJ/mol) [ 3 ], commercial AZ80 alloy (216 kJ/mol) [ 36 ], extruded-state α(Mg)–β(Li) duplex phase Mg–Li alloy (148 kJ/mol) [ 37 ], as-cast Mg–2 Zn–0.3 Zr–0.9 Y alloy (236.2 kJ/mol) [ 38 ], and as-cast Mg–3 Sn–Ca alloy (236 kJ/mol) [ 39 ]. Despite being related to the other Mg–Li alloys with α + β duplex phases or a single β -phase, the deformation activation energy in the presented work was higher than those of the as-cast α + β alloy (127 kJ/mol) [ 40 ], the as-cast single β -phase Mg–Li alloy (95 kJ/mol) [ 41 ], the as-cast Mg–8 Li–3 Al–2 Zn alloy modified with Zr (108 kJ/mol) [ 8 ], the as-cast Mg–9 Li–1 Zn alloy (127 kJ/mol) [ 42 ], the as-cast Mg–11.5 Li–1.5 Al alloy (95 kJ/mol) [ 43 ], the as-cast Mg–3 Sn–2 Al–1 Zn–5 Li (139 kJ/mol) [ 44 , 45 ], the as-cast Mg–9 Li–3 Al alloy with Sr addition (110 kJ/mol) [ 46 ], and as-cast LA43M (110 kJ/mol) [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…From Figure 7, it can be found that the elongations of all the samples were more than 100%, indicating the appearance of the superplasticity. In the process of the high temperature deformation, the grain boundary sliding and atomic free energy can be promoted by the increasing appropriate deformation temperature, resulting in the increase of the diffusional creep ability and superplasticity [39]. The grain coarsening generated when the deformation temperature was higher than 450 • C, therefore, the elongation decreased.…”
Section: The Effect Of Deformation Parameters On the Deformation Beha...mentioning
confidence: 99%